2015
DOI: 10.1159/000444758
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Fibrosing Alopecia and Increased Scalp Sweating: Is Neurogenic Inflammation the Common Link

Abstract: Frontal fibrosing alopecia (FFA) is an uncommon scarring hair loss disorder that is characterized by a band-like recession of the frontal hair line with eyebrow hair loss. We present a series of patients with FFA and increased sweating predominantly localized to the scalp, and potential explanations for this association are discussed. We hypothesize that the reported increase in sweating seen in our patients may be in part related to the inflammatory process occurring locally within the skin, either inducing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In contrast, intensity of subjective symptoms such as pruritus, pain and burning was comparable among men and women, highlighting the impact of the disease on life quality and the importance of addressing subjective symptoms during patient interview, especially in male patients, even if dermatoscopic examination shows less or no clinical disease activity signs. According to data from this patient collective, most conclusive markers for disease activity were the presence of perifollicular erythema and hyperkeratosis, pruritus as well as skin erythema and increased scalp sweating . Increased sweating of the scalp, which is mediated by neurogenic mediators, has been reported before and possibly suggests a role of neurogenic inflammation in the pathogenesis of the disease …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In contrast, intensity of subjective symptoms such as pruritus, pain and burning was comparable among men and women, highlighting the impact of the disease on life quality and the importance of addressing subjective symptoms during patient interview, especially in male patients, even if dermatoscopic examination shows less or no clinical disease activity signs. According to data from this patient collective, most conclusive markers for disease activity were the presence of perifollicular erythema and hyperkeratosis, pruritus as well as skin erythema and increased scalp sweating . Increased sweating of the scalp, which is mediated by neurogenic mediators, has been reported before and possibly suggests a role of neurogenic inflammation in the pathogenesis of the disease …”
Section: Discussionmentioning
confidence: 54%
“…According to data from this patient collective, most conclusive markers for disease activity were the presence of perifollicular erythema and hyperkeratosis, pruritus as well as skin erythema and increased scalp sweating . Increased sweating of the scalp, which is mediated by neurogenic mediators, has been reported before and possibly suggests a role of neurogenic inflammation in the pathogenesis of the disease …”
Section: Discussionmentioning
confidence: 54%
“…The proposed HF–ESG association may also be clinically relevant, as it may help us to understand better the sweat gland alterations that have been reported in selected forms of alopecia, including excessive localized hyperhidrosis in patients with frontal fibrosing alopecia and the increased number and volume of ESGs in androgenetic alopecia scalp skin . Also, future research into wound healing and selected skin diseases (involving one of the components discussed here) should routinely consider the adnexal skin unit concept.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the association between hair growth and anti-inflammatory effects, it has been reported that the suppression of inflammation improves the condition of the scalp, and suppresses apoptosis in HDPC. 21,22.…”
Section: Discussionmentioning
confidence: 99%